PERAN PENDIDIKAN ISLAM DALAM KELUARGA UNTUK MENUMBUHKAN KEPRIBADIAN ANAK USIA 6-12 TAHUN - Komariyah, Siti; Nuraini, Siti; Khamdiyah, Siti; Fatimah, Siti; Seriwanti, Seriwanti; Wahyuningsih, Sila Sakti Sri (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Children are a mandate from Allah SWT that must be guarded and nurtured, their pure hearts are like precious gems. If they are accustomed to evil and left like animals, they will be harmed and destroyed. While maintaining them is through educational efforts and teaching them good morals. Which aims for children to have perfect personalities with a pattern of piety that is useful both for themselves and for society, and are happy and fond of practicing the teachings of Islam in their relationship with the creator, fellow humans with the environment and with themselves in order to achieve happiness and safety in life in the world and in the hereafter. To obtain data in this study, the author uses the library research method, so data collection is carried out by reading, reviewing books, magazines, newspapers and other information materials, which are related to this discussion. In writing this thesis, the author focuses on the problems of Islamic Education and Islamic Psychology. The results related to writing this research are the position of the family in children's education is the determinant or foundation of the child's personality. Children are born in a pure state. From the family environment, one of the dominant ones is that the child's personality will grow and develop. Education carried out by parents through the process of teaching, coaching, training, instilling religious values, nurturing and responsibility to be directed towards a good and noble direction and habits, both physically and spiritually continuously and gradually. The role of Islamic education in shaping the child's personality is emphasized on the aspects of faith, worship, and morals which are applied in the form of exemplary behavior carried out by parents. From this exemplary behavior, children will understand that the implementation of religious teachings must be truly implemented.